Performance of the WHO 2011 TB Symptom Screening Algorithm for Pulmonary TB Diagnosis among HIV-Infected Patients in Gondar University Referral Hospital, Ethiopia - Martha Alemayehu Menberu (International Journal of Microbiology)
The new WHO 2011 guidelines on TB screening among HIV-infected individuals recommend screening using four TB symptoms (current cough, fever, weight loss, and night sweats). This study aimed to assess the performance of WHO 2011 TB symptom screening algorithm for diagnosing pulmonary TB in HIV patients and identify possible risk factors for TB. Institutional based cross-sectional study was conducted from February 2012 to November 2012. A total of 250 HIV-infected patients aged ≥18 years visiting the University of Gondar Hospital, ART clinic, were enrolled. Information about WHO TB clinical symptoms and other known risk factors for TB was collected using structured questionnaire. Spot-morning-spot sputum samples were collected and direct AFB microscopy, sputum culture, and RD9 molecular typing were performed. Statistical data analysis was performed using SPSS Version 20.0 software. Of 250 study participants, fever was reported in 169 (67.6%), whereas cough and night sweats were reported in 167 (66.8%) and 152 (60.8%), respectively. A total of 11 (4.4%) TB cases were identified. Of these, 82% (9/11) TB patients reported cough, so that the negative predictive value was 98%. In addition, 66% (158/239) TB negative patients reported cough, so that positive predictive value of cough was 5%. According to the new WHOTB symptom screening algorithm, out of 250 HIV-infected persons, 83% (5/6) have been investigated by TB symptom screening and AFB smear microscopy. Therefore, the 2011 WHO TB symptom screening tool for the diagnosis of pulmonary TB is likely to reduce the diagnostic delay and lower TB morbidity and mortality rate particularly in HIV prevalent settings.